Enzyme responsive mesoporous silica nanoparticles for targeted tumor therapy in vitro and in vivo. Issue 8 (30th January 2015) - Liu, Junjie; Zhang, Beilu; Luo, Zhong; Ding, Xingwei; Li, Jinghua; Dai, Liangliang; Zhou, Jun; Zhao, Xiaojing; Ye, Jingya; Cai, Kaiyong
Abstract : A tumor microenvironment enzyme-responsive drug delivery system based on mesoporous silica nanoparticles is fabricated for targeted tumor therapy in vitro and in vivo . Abstract : This study reports a biocompatible controlled drug release system based on mesoporous silica nanoparticles (MSNs) for tumor microenvironment responsive drug delivery. It was fabricated by grafting phenylboronic acid conjugated human serum albumin (PBA-HSA) onto the surfaces of MSNs as a sealing agent, via an intermediate linker of a functional polypeptide, which was composed of two functional units: the polycation cell penetrating peptide (CPP) polyarginine, and matrix metalloproteinase 2 (MMP-2) substrate peptide. A series of characterizations confirmed that the system had been successfully constructed. In vitro tests proved that the anticancer drug loading system could efficiently induce cell apoptosis in vitro . More importantly, the in vivo tumor experiments confirmed that the anticancer loading system could efficiently inhibit tumor growth with minimal side effects.